2001
DOI: 10.1348/096317901167451
|View full text |Cite
|
Sign up to set email alerts
|

The practitioner‐researcher divide in Industrial, Work and Organizational (IWO) psychology: Where are we now, and where do we go from here?

Abstract: There is current concern that the researcher, or academic, and the practitioner wings of our discipline are moving further apart. This divergence is likely to result in irrelevant theory and in untheorized and invalid practice. Such outcomes will damage our reputation and ultimately result in our fragmentation. We present a simple 2 × 2 model along the dimensions of relevance and rigour, with the four cells occupied by Popularist, Pragmatic, Pedantic, and Puerile Science, respectively. We argue that there has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
346
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(372 citation statements)
references
References 17 publications
5
346
0
6
Order By: Relevance
“…The gap between science and practice has been much lamented within the social sciences generally and the field of W&O psychology in particular (e.g., Anderson, Herriot, & Hodgkinson, 2001). Despite the long history of debate over the issue, there remains disagreement over the nature, extent, and possible causes of the gap (e.g., Anderson, 2007;Guest, 2006).…”
mentioning
confidence: 99%
“…The gap between science and practice has been much lamented within the social sciences generally and the field of W&O psychology in particular (e.g., Anderson, Herriot, & Hodgkinson, 2001). Despite the long history of debate over the issue, there remains disagreement over the nature, extent, and possible causes of the gap (e.g., Anderson, 2007;Guest, 2006).…”
mentioning
confidence: 99%
“…In the third stage reviewers formulate recommendations in a form that can be easily applied in practice, for example in protocols or checklists. Protocols or checklists are ways in which pragmatic science (as explained in Section 1 and defined by Anderson et al, 2001) can be communicated, for example to practitioners.…”
Section: Literature Reviews Of Management Accounting Researchmentioning
confidence: 99%
“…Equivalently, producing management accounting theory that is more useful for practitioners implies that there should be a well-functioning nexus between the contributing disciplines (the social sciences) used by academic researchers and the management accounting tools and techniques that practitioners need to deal with practical issues. Anderson et al (2001) proposed a classification of applied social sciences, consisting of four types and this classification is based on the following two dimensions: theoretical and methodological rigor (which is either "high" or "low") and practical relevance (also "high" or "low"). "Popularist science," the first type, is low on theoretical and methodological rigor and high on practical relevance.…”
mentioning
confidence: 99%
“…Instead, it is likely that most I-O psychologists would primarily be concerned with either research or practice, with only a secondary concern for the other piece of the model. Anderson, Herriot, and Hodgkinson (2001) observed that those on both sides of the science-practice gap in I-O psychology hold stereotypes of one another. Researchers are seen as interested only in methodology at the expense of anything relevant to the real world, whereas practitioners are seen as proponents of fads, ignoring all theoretical evidence.…”
mentioning
confidence: 99%
“…As for autonomy, academic freedom is a crucial part of research within a university. The academic setting is characterized by little monitoring and academic independence (Anderson et al, 2001). One might expect that people drawn to academic careers would place a higher value on autonomy than those drawn to applied careers.…”
mentioning
confidence: 99%